Inflammasomes in Inflammation-Induced Cancer - Lin, Chu; Zhang, Jun (Frontiers in Immunology, 2017)
The inflammasome is an important multiprotein complex that functions during inflammatory immune responses. The activation of inflammasome will lead to the autoactivation of Capase-1 and subsequent cleavage of proIL-1β and proIL-18，which are key sources of inflammatory manifestations. Recently, the roles of inflammasomes in cancers have been extensively explored, especially in inflammation-induced cancers. In different and specific contexts, inflammasomes exhibit distinct and even contrasting effects in cancer development. In some cases, inflammasomes initiate carcinogenesis through the extrinsic pathway and maintain the malignant cancer microenvironment through the intrinsic pathway. On the contrary, inflammasomes also exert anti-cancer effects by specialized programmed cell death called pyroptosis and immune regulatory functions. The phases and compartments in which inflammasomes are activated strongly influence the final immune effects. We systemically summarize the functions of inflammasomes in inflammation-induced cancers, especially in gastrointestinal and skin cancers. Besides, information about the current therapeutic use of inflammasome-related products and potential future developing directions are also introduced.